Ahlussunah wal jamaah perspektif hasyim asy’ari - Muhamad Wildan Nasirudin, Muhammad Avidh Ni’ama , Ahmad Hanafi Rozak, (Majelis Pembinaan Kader Sumber Daya Insani Pimpinan Daerah Muhammadiyah Kota Salatiga, 2023)
Ahlussunnah wal jamaah is a phrase that describes a people who follow the teachings of the prophet and his companions, but in this context ahlussunnah wal jamaah is in the theological sphere. Ahlussunnah waljamah refers to the thoughts of Abu Hasan Al Asy'ari and Abu Mansur Al Maturidi. The purpose of making this journal is to find out the big picture of ahlussunnah wal jamaah from the perspective of Hasyim Asy'ari. Data processing is carried out using the qualitative method with litetarure review type method. The research results obtained by the author that there are two reasons that make ahlussunnah wal jamaah the theological foundation from Hasyim Asy'ari's perspective,first ahlussunnah wal jamaah as the majority group this statement come from hadith “Indeed, Allah has protected my people from agreeing on misguided” and second ahlussunnah wal jamaah as a contemporary mazhab that are able to answer the problems according to the challenges of the times.